Lyric post-modernizm by Nazli Eray - M M Repenkova (RUDN Journal of Studies in Literature and Journalism, 2009)
The article investigates the typological peculiarities of Turkish lyric post-modernizm on the example of the novel Nazli Eray «The Station of Dream» and it took one of the central places of the country. A special attention is paid to the author ̉s mask by means of which the author ̉s self-expression is realized.